What Role Does the Prefrontal Cortex Play in the Processing of Negative and Positive Stimuli in Adolescent Depression? - Kaya, Siyabend (Brain Sci, 2019)
This perspective describes the contribution of the prefrontal cortex to the symptoms of depression in adolescents and specifically the processing of positive and negative information. We also discuss how the prefrontal cortex (PFC) activity and connectivity during tasks and at rest might be a biomarker for risk for depression onset in adolescents. We include some of our recent work examining not only the anticipation and consummation of positive and negative stimuli, but also effort to gain positive and avoid negative stimuli in adolescents with depression. We find, using region of interest analyses, that the PFC is blunted in those with depression compared to controls across the different phases but in a larger sample the PFC is blunted in the anticipatory phase of the study only. Taken together, in adolescents with depression there is evidence for dysfunctional PFC activity across different studies and tasks. However, the data are limited with small sample sizes and inconsistent findings. Larger longitudinal studies with more detailed assessments of symptoms across the spectrum are needed to further evaluate the role of the PFC in adolescent depression.